Pengembangan Media Pembelajaran DUGIBO untuk Mengasah Keterampilan Membaca Siswa Kelas 5 MI Ma’arif Kadipaten Ponorogo: Development of DUGIBO Learning Media to SharpenReading Skills of Grade 5 Students of MI Ma'arif Kadipaten Ponorogo - Rosita, Farida Yufarlina; Istiqomah, Istiqomah (Universitas Nusantara PGRI Kediri, 2024)
This research addressed the need for engaging and effective learning media in Indonesian language education, focusing on improving reading comprehension skills among fifth-grade students. Recognizing the limitations of standard worksheets, the study developed and validated the Education Gift Box (DUGIBO), a learning tool designed to teach main idea identification within environmental insight texts. Employing a research and development approach using the 4D model, the study aimed to assess the validity of DUGIBO as a viable educational resource. Data were collected through interviews, observations, questionnaires, and documentation, involving an expert validator, a stakeholder teacher, and 21 students from class 5A at MI Ma'arif Kadipaten Ponorogo. The evaluation encompassed media, material, and language aspects, with data analyzed using percentage correction formulas. The findings revealed that the expert validation yielded a